Transparansi Keuangan Daerah Dalam Era Desentralisasi Fiskal: Tinjauan Manajemen Keuangan Daerah - Azfirmawarman, Dony; Asnil, Asnil; Frinaldi, Aldri; Putri, Nora Eka (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2024)
This study explores the urgency of implementing transparency in regional financial management in the era of fiscal decentralization in Indonesia. Using a qualitative descriptive approach, this study explains how the principles of transparency and accountability can support more effective financial management at the regional level. The findings show that regional financial transparency encourages public trust, community participation, and more effective budget oversight. However, there are a number of challenges that hinder implementation, such as limited human resource capacity, inadequate technological infrastructure, and low political commitment. Therefore, this study recommends developing human resource capacity, optimizing information technology, and increasing the commitment of regional governments to strengthen regional financial transparency.